2000
DOI: 10.1038/sj.bjp.0703615
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT4 receptors on cholinergic nerves involved in contractility of canine and human large intestine longitudinal muscle

Abstract: 1 5-HT 4 receptors mediate circular muscle relaxation in both human and canine large intestine, but this phenomenon alone can not explain the improvement in colonic motility induced by selective 5-HT 4 receptor agonists in vivo. We set out to characterize 5-HT 4 receptor-mediated e ects in longitudinal muscle strips of canine and human large intestine. 2 Electrical ®eld stimulation (EFS) was applied providing submaximal isotonic contractions. L-NOARG (0.1 mM) was continuously present in the organ bath to precl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 25 publications
(26 reference statements)
4
96
0
2
Order By: Relevance
“…These effects of DKT on isolated intestine provide a pharmacological basis for recovery from morphine-induced disorder of GI transit. It has been recently demonstrated that GI transit may be coordinated by relaxation of the circular muscle and constriction of the longitudinal muscle through several neuronal networks including serotonin receptors (8,9). This supports the previous work of Grider and Makhlouf who showed that morphine slows GI transit by inhibiting relaxation of the circular muscle and contraction of the longitudinal muscle (10).…”
supporting
confidence: 80%
“…These effects of DKT on isolated intestine provide a pharmacological basis for recovery from morphine-induced disorder of GI transit. It has been recently demonstrated that GI transit may be coordinated by relaxation of the circular muscle and constriction of the longitudinal muscle through several neuronal networks including serotonin receptors (8,9). This supports the previous work of Grider and Makhlouf who showed that morphine slows GI transit by inhibiting relaxation of the circular muscle and contraction of the longitudinal muscle (10).…”
supporting
confidence: 80%
“…The effects such as inhibition of ileum contractions, slowing motility and propulsion of intraluminal contents are generally known to take part in anti-transit effect (Shook et al, 1989). Gastrointestinal (GI) transit may be coordinated by relaxation of the circular muscle and constriction of the longitudinal muscle (Prins et al, 2000;Shibata et al, 1999). Nerve supply of GI tract has two types, enteric system (myenteric and submucosal plexus) and extrinsic nerves (parasympathetic and sympathetic nerves).…”
Section: Discussionmentioning
confidence: 99%
“…Прукалоприд стимулирует сокращения в продольных гладких мышцах толстой кишки путем стимулирования высвобождения ацетилхолина посредством активации рецепторов 5-НТ 4 на пресинаптических холинергических кишечных нейронах [33]. Прукалоприд также индуцирует релаксацию толстой кишки за счет продольных гладких мышц и прямой кишки человека через локальную актива-цию 5-HT 4 -рецепторов [34].…”
Section: фармакология и механизм действияunclassified